DESIGNING AN ELECTROMECHANICAL GENERATOR FOR ENERGY HARVESTING - Pranjić, Franjo; Smolar, Nejc; Virtič, Peter (Journal of Energy Technology, 2023)
Five different designs of tubular electromechanical generator for low frequency energy harvesting have been investigated in this paper. In order to design a simple and robust generator, models were constructed out of permanent magnets, steel and windings. In all five generator models, round movers were used in spherical and cylindrical form- for four models solely permanent magnets were used, and in one model, there was steel present in the mover. The movers are slid or rolled through a tube, and induce voltage in the stator winding. All windings were constructed with the same cross- -section dimensions and number of turns. To compare different models, 3D analysis with the Finite Element Method was performed, in order to determine the magnetic flux through the windings. The induced voltage was calculated using the results of the analysis. As a result of the different winding geometries, the average turn length varied for the different designs, subsequently altering resistance and inductance, which affected the generator`s power output and losses. To simulate the generator`s dynamics, an equivalent circuit model was constructed using the Simulink software and data obtained previously from a 3D electromagnetic analysis. With the Simulink model, we coupled the mechanical and electrical systems together to acquire the harvester yields.